2020
DOI: 10.1097/mnm.0000000000001264
|View full text |Cite
|
Sign up to set email alerts
|

RET gene mutation analysis and long-term clinical outcomes of medullary thyroid cancer patients

Abstract: Objective Medullary thyroid carcinoma is a rare, potentially aggressive tumour, with relatively worse prognosis than well-differentiated thyroid cancer. We evaluated the long-term outcomes and prognosis of medullary thyroid carcinoma patients at a single institution in India and compared outcomes based on results of RET protooncogene mutation analysis. Methods Data were retrieved through a prospectively maintained thyroid cancer database from 1998 to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Until now, univariate and multivariate analyses have both revealed LNM played a significant role in predicting disease recurrence 11 . Presence of LNM can cause five times more likely to relapse than the absence of LNM 11,13 . The study of Lee et al 14 found that the deaths can be up to 16 patients, who died of distant metastasis or locoregional failure, among 18 patients with recurrence, nearly 89% 14 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Until now, univariate and multivariate analyses have both revealed LNM played a significant role in predicting disease recurrence 11 . Presence of LNM can cause five times more likely to relapse than the absence of LNM 11,13 . The study of Lee et al 14 found that the deaths can be up to 16 patients, who died of distant metastasis or locoregional failure, among 18 patients with recurrence, nearly 89% 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of Nie et al 12 also found that the rate of lateral LNM and central LNM were 74.9% and 70.5%, respectively, in PTC patients in China. Until now, univariate and multivariate analyses have both revealed LNM played a significant role in predicting disease recurrence 11 . Presence of LNM can cause five times more likely to relapse than the absence of LNM 11,13 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations